Preliminary validation of 2 magnetic resonance image scoring systems for osteoarthritis of the hip according to the OMERACT filter - Maksymowych, Walter P.; Cibere, Jolanda; Loeuille, Damien; Weber, Ulrich; Zubler, Veronika; Roemer, Frank; Jaremko, Jacob L.; Sayre, Eric C.; Lambert, Robert G. W. (Journal of Rheumatology, 2014)
Development of a validated magnetic resonance image (MRI) scoring system is essential in hip OA because radiographs are insensitive to change. We assessed the feasibility and reliability of 2 previously developed scoring methods: (1) the Hip Inflammation MRI Scoring System (HIMRISS) and (2) the Hip Osteoarthritis MRI Scoring System (HOAMS).Six readers (3 radiologists, 3 rheumatologists) participated in 2 reading exercises. In Reading Exercise 1, MRI of the hip of 20 subjects were read at a single time point followed by further standardization of methodology. In Reading Exercise 2, MRI of the hip of 18 subjects from a randomized controlled trial, assessed at 2 timepoints, and 27 subjects from a cross-sectional study were read for HIMRISS and HOAMS bone marrow lesions (BML) and synovitis. Reliability was assessed using intraclass correlation coefficient (ICC) and kappa statistics.Both methods were considered feasible. For Reading 1, HIMRISS ICC were 0.52, 0.61, 0.70, and 0.58 for femoral BML, acetabular BML, effusion, and total scores, respectively; and for HOAMS, summed BML and synovitis ICC were 0.52 and 0.46, respectively. For Reading 2, HIMRISS and HOAMS ICC for BML and synovitis-effusion improved substantially. Interobserver reliability for change scores was 0.81 and 0.71 for HIMRISS femoral and HOAMS summed BML, respectively. Responsiveness and discrimination was moderate to high for synovitis-effusion. Significant associations were noted between BML or synovitis scores and Western Ontario and McMaster Universities Osteoarthritis Index pain scores for baseline values (p <= 0.001).The BML and synovitis-effusion components of both HIMRISS and HOAMS scoring systems are feasible and reliable, and should be validated further.
EVALuna2:14465